The procrastination influence on academic performance and the moderating role of personal sense of power - Elder Semprebon; Hugo Dias Amaro; Ilse Maria Beuren (Arizona State University, 2017)
This study aims to verify the procrastination influence on undergraduate students' academic performance, regarding the sense of power as a moderator variable. A descriptive research was carried out from a survey sample of 469 students registered in Accounting Sciences, Economic Sciences, Administration, Marketing and Tourism courses, enrolled in a private undergraduate institution. The data collected was analyzed through descriptive statistics, multivariate tests and structural equations modeling. Results indicated that procrastination exerts a negative and significant influence on students' academic performance (H1). In order to broaden understanding, a moderation analysis of the model was conducted and it was found that the direct negative effect occurs under limited conditions, since the procrastination influence happens only among subjects with a low sense of power (H2). Therefore, the present results enhance the study of procrastination influence on academic performance by highlighting its relation with the moderating role of the sense of power.